Full quantum search for high Tc two-dimensional van der Waals ferromagnetic semiconductors. Issue 17 (21st April 2021) - Liu, Liang; Lin, Zezhou; Hu, Jifan; Zhang, Xi
Abstract : High throughput and accurate screening of 2D ferromagnetic semiconductors was conducted, predicting superior candidates and unveiling the crucial roles of quantum effects in 2D magnetism. Abstract : Atomic thin two-dimensional (2D) ferromagnetic (FM) semiconductors with high Curie temperatures ( T c ) are essential for future spintronic applications. However, reliable theoretical searching for 2D FM semiconductors is still hard due to the complexity of strong quantum fluctuations in 2D systems. We have proposed a full quantum search (FulQuanS) method to tackle the difficulty, and finally identified five 2D semiconductors of CrX3 (X = I, Br, Cl), CuCl3 and FeCl2 with FM order at finite temperature from the pool of 3721 potential 2D structures. Via the method of renormalized spin wave theory (SW) and quantum Monte Carlo simulations (QMC), we located the T c for CrX3 (X = I, Br, Cl), CuCl3 and FeCl2 at 48 K, 31 K, 18 K, 74 K and 931 K respectively, which excellently agree with experiments for CrX3 and reveal the superior performances of the new predicted structures. Furthermore, our QMC results demonstrated that the systems with low-spin numbers and/or low anisotropies have much higher T c than the estimations of classical models e.g., Monte Carlo simulations based on classical Heisenberg models. Our findings suggest excellent candidates for future room-temperature spintronics, and shed light on the quantum effects inherent in 2D magnetism.